Sources on art technology. Back to basics proceedings of the sixth symposium of the ICOM-CC working group for art technological source research, held at the Rijksmuseum, Amsterdam, 16-17 June 2014 - Eyb-Green, Sigrid 1974-; Townsend, Joyce H.; Pilz, Kathrin; Kroustallis, Stefanos; Leeuwen, Idelette van (Archetype Publications, 2016)
A collection of papers from the 2014 biennial ATSR symposium investigating the uses of source material for historical research and the conservation of art today.0